Sorafenib as first-line therapy for metastatic uveal melanoma: A multicenter, placebo-controlled randomized discontinuation study (STREAM) - Kalkavan, Halime; Scheulen, Max E.; Kämpgen, Eckhart; Keilholz, Ulrich; Heinzerling, Lucie; Lueong, Smiths S.; Hlinka, Annalena; Gromke, Tanja; Ochsenreither, Sebastian; Hilger, Ralf Axel; Grubert, Matthias; Wetter, Axel; et al. (iScience, 2025)
Almost every second patient with uveal melanoma develops metastatic disease, with a usually fatal outcome within one year. The scarcity of broadly applicable systemic therapies further limits patient survival. In this multicenter, placebo-controlled randomized discontinuation phase 2 trial, we evaluated the efficacy of the multi-kinase inhibitor sorafenib in treatment-naïve patients with metastatic uveal melanoma (mUM). After a 56-day run-in period with 400 mg bid sorafenib in a total of 147 patients, randomization was performed in 78 patients with stable disease assigned to blinded sorafenib or placebo in a 1:1 ratio. The primary endpoint of the study was met with a significantly higher median progression-free survival (PFS) in the sorafenib group compared to placebo (5.5 vs. 1.9 months, HR = 0.53, p = 0.0083). First-line treatment with sorafenib was well tolerated and showed promising efficacy in patients with mUM. The detection of GNAQ/GNA11 mutations in ctDNA at baseline was associated with an inferior outcome. (ClinicalTrials.gov: NCT01377025).
CRIS-Team Scopus Importer:2025-12-05
Keywords: Health sciences; medical specialty; Medicine; oncology